Silicone-based composite materials simulate breast tissue to be used as ultrasonography training phantoms - (:unkn) unknown (ELSEVIER, 2018)
A silicone-based composite breast phantom is fabricated to be used as an education model in ultrasonography training. A matrix of silicone formulations is tracked to mimic the ultrasonography and tactile response of human breast tissue. The performance of two different additives: (i) silicone oil and (ii) vinyl-terminated poly (dimethylsiloxane) (PDMS) are monitored by a home-made acoustic setup. Through the use of 75 wt% vinyl-terminated PDMS in two-component silicone elastomer mixture, a sound velocity of 1.29 +/- 0.09 x 10(3) m/s and an attenuation coefficient of 12.99 +/- 0.08 dB/cm-values those match closely to the human breast tissue-are measured with 5 MHz probe. This model can also be used for needle biopsy as well as for self-exam trainings. Herein, we highlight the fabrication of a realistic, durable, accessible, and cost-effective training platform that contains skin layer, inner breast tissue, and tumor masses. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Breast phantom; Tissue mimicking; Breast ultrasonography; Silicone composites; ULTRASOUND; CANCER; MAMMOGRAPHY; DISEASES; COMMON; WOMEN; MRI